(untitled) (Letras, 2019)
The Spanish Professor and researcher Miguel Ángel Garrido Gallardo, who is considered one of the leading European specialists in Literary Theory, has kindly volunteered to be interviewed by Letras to expose and explain a series of issues regarding the study of lyric discourse. We are honored to offer our readers his thorough overview of lyric poetry theories, analytical methodologies and new research perspectives, with particular focus on the Hispanic context.